Strategic Development and SWOT Analysis of Canting Batik Industry - Astuti, Diah; Masrifah, Ifah; Basir, M. Abdul; Lestari, Etty Puji (Archives of Business Research, 2021)
The development of canting batik industry has lagged, and the number has decreased compared to the batik industry. This industry is believed to have a potential passive market and can provide job opportunities for local workers, reducing urbanization. Based on this background, this research is needed to analyze the potential and innovation of canting batik industry in Central Java, Indonesia. We choose Central Java, based on the fact that the batik industries grew most in Pekalongan, Central Java. The article uses qualitative research. We use Focus Group Discussion and direct observation to map the competitiveness of SMEs. To see the most significant opportunities and challenges, we also use a SWOT analysis. The results of this study indicate that the growth of the canting stamped batik industry is relatively slow. Some of its causes are relatively expensive raw materials, low product demand, and local government support. SME players can use some strategies to make canting as a souvenir product, looking for alternative ways to non-brass raw materials, and cooperating with complementary industries, including the batik industry.